2017
DOI: 10.1039/c7ra08162f
|View full text |Cite
|
Sign up to set email alerts
|

Large magnetocaloric effect and critical behavior in La0.7Ba0.2Ca0.1Mn1−xAlxO3

Abstract: The structural, magnetic and magnetocaloric properties of La0.7Ba0.2Ca0.1Mn1−xAlxO3 (0 ≤ x ≤ 0.1) perovskite manganite oxides have been investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 49 publications
0
3
0
1
Order By: Relevance
“…The value of θ p (θ p = -36 K) is negative, underlining the appearance of an AFM interaction between Cr 3+ ions. We have inferred the effective moment experimental μ eff xp values from the Curie constant employing the following relationship represented as [3]:…”
Section: Methods Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The value of θ p (θ p = -36 K) is negative, underlining the appearance of an AFM interaction between Cr 3+ ions. We have inferred the effective moment experimental μ eff xp values from the Curie constant employing the following relationship represented as [3]:…”
Section: Methods Resultsmentioning
confidence: 99%
“…On the other hand, the increase above 25 K is probably due to the second phase transition, which was not apparent when the structure of KCrP The magnetic refrigeration capacity (RCP) is a critical metric for an essential feature of the MCE; it is connected with the application of magnetic refrigerators. To evaluate RCP, we also used the following formula [7]:…”
Section: Methods Resultsmentioning
confidence: 99%
“…另外, 在对典型具备一级相变的La 0.7 Ca 0.3 MnO 3 多晶材 料施加超高场的磁性研究中发现, 当磁场强度达 到10-14 T范围时, 其一级相变特性被明显抑制, 且磁相变临界参数与三重临界点十分符合 [85] . 而 Ghorai等 [86] [45] 在5 T磁场 变化下, 最大等温磁熵变仍达到了14.94 J•kg -1 •K -1 . 而微量Sn掺杂的La 0.7 Ca 0.28 Sn 0.02 MnO 3 化合物 [46] 在仅为1 T磁场变化下的最大磁熵变仍保持了 2.79 J•kg -1 •K -1 , 且相对制冷能力达到55.8 J•kg -1 .…”
Section: 不同磁场强度范围所得磁相变临界 参数对比分析unclassified
“…This indicates that the strength of the competing exchange interactions and magnetic properties are eventually affected by different factors such as rare Earth substitution at the A-site, replacement of manganese by other transition elements, the introduction of deciency at A and A 0sites, etc. [28][29][30][31][32][33][34][35][36][37] Recently, many reports have demonstrated that the creation of deciency at the rare Earth and alkaline rare Earth sites alter the Mn 2+ /Mn 3+ /Mn 4+ ratio which severely affect the magnetic and magnetocaloric properties. [37][38][39][40][41][42][43][44][45][46][47][48][49] The structure of manganites is imperfect and contain vacancy type point defects, called Schottky defects due to the cyclic temperature changes during synthesis and sintering process.…”
Section: Introductionmentioning
confidence: 99%